The Effect of Different Fertilizer Applications on Cotton (Gossypium hirsutum L.) Dry Matter Accumulation And its Effect on Physiological Parameters - BEYYAVAŞ, Vedat; NUR YILMAZ, Şevin; CUN, Suat (ISPEC Journal of Agricultural Sciences, 2022)
In this study, Candia variety was used according to the randomized block plots experimental design in Şanlıurfa-Harran conditions in 2021 and was carried out with 3 replications. Each parcel consisted of 5 rows, the parcel length was 12 m, the row spacing was 70 cm, and the row spacing was 10-12 cm. The experiment consisted of a total of 24 plots. In the study, applications consisting of mixtures of different chemical and organic fertilizers were applied. These are 1-Control, 2-Base fertilizer (0 kg)+Top fertilizer (Urea 20 kg+15 kg/da) 35 kg/da in total, 3-Base fertilizer (10 DAP/da)+Top fertilizer (Urea 20 kg/da) +15 kg/da) 35 kg/da in total, 4-Base fertilizer (20 DAP/da)+Top fertilizer (Urea 20 kg+15 kg/da) 35 kg/da in total, 5-Base fertilizer (30 DAP/da) )+Top fertilizer (Urea 20 kg+15 kg/da) in total 35 kg/da, 6-Base manure (2 tons farm fertilizer/da)+ Top fertilizer (Urea 20 kg+15 kg/da) in total 35 kg/da, 7-Base manure (4 tons farm fertilizer/da)+Top manure (Urea 20 kg+15 kg/da) 35 kg/da in total, 8-Base manure (6 tons farm fertilizer/da)+Top fertilizer (Urea 20 kg+15 kg/da) consisted of a total of 35 kg/da subjects. Physiological parameters were examined on 5 plants from each plot during the growth periods of the plant (60th day, 75th day, 90th day, 105th day and 120th day) after planting. Plant height (cm), number of nodes (piece/plant), HNR, leaf dry matter (g), stem dry matter (g), flower and boll dry matter (g) and total dry matter weights were measured during the growth stages. In our study; When the development period is examined, we see that as the number of days increases, the total dry matter accumulation increases proportionally, and there is a direct proportional increase in total dry matter T1<T2<T3<T4<T5 (from the vegetative period to the end of the generative period).